Struktur Naratif Labov dan Bentuk Reflektif dalam Kisah Reflektif di Siniar Youtube - Ariyadi; Suhartono (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the narrative structure that constructs the reflective narratives and to identify the forms of reflection employed. Employing a qualitative approach, this research utilizes narrative discourse analysis. The data source consists of reflective narratives from the Escape podcast. The analysis was conducted in two stages. First, all transcripts were mapped onto William Labov's six elements of narrative structure. Second, the evaluation, resolution, and coda elements were analyzed using a classification of four reflective forms synthesized from the theories of John Dewey, Donald Schön, Jennifer Moon, and Jack Mezirow. The findings reveal that the reflective narratives in the Escape podcast include complete narrative structures that are coherent, complete narrative structures that are incoherent, as well as incomplete narrative structures. Furthermore, the findings on reflective forms were predominantly characterized by learning reflection, followed by self-awareness reflection, evaluative reflection, and transformative reflection as the least frequently observed form. These findings indicate that the narrators in the Escape podcast exhibit a gradation of reflective depth, progressing from merely acknowledging internal conditions to declaring fundamental shifts in perspective.